PEMANFAATAN HASIL PENELITIAN LINGUISTIK PEDAGOGIS DALAM PENINGKATAN KUALITAS PEMBELAJARAN DI SEKOLAH - Widiatmoko, Bambang (Turats, 2009)
The improvement of quality of learning activity in the school can be applied through many ways, one of them is accomodate result of research on pedagogical aims. In those days, both the teachers and other educational practitioners have not yet accommodate those result seriously. Due to it, it is essential to push the teacher and educational practitioner to accommodate those research?s result. In this paper the writer is describes the urgent of accommodate research result in pedagogical objectives due to improve the school?s learning process quality. The analysis is refered to three kinds of theory on learning process, i.e. behavioral approach, gestalt approach, and constructivist approach.